The Host Restriction Factor Interferon-Inducible Transmembrane Protein 3 Inhibits Vaccinia Virus Infection - Li, Chang; Du, Shouwen; Tian, Mingyao; Wang, Yuhang; Bai, Jieying; Tan, Peng; Liu, Wei; Yin, Ronglan; Wang, Maopeng; Jiang, Ying; Li, Yi; Zhu, Na; et al. (Frontiers in Immunology, 2018)
Interferons (IFNs) establish dynamic host defense mechanisms by inducing various IFN-stimulated genes (ISGs) that encodes many antiviral innate immune effectors. IFN-inducible transmembrane (IFITM) proteins have been identified as intrinsic antiviral effectors, which block the entry of a broad spectrum of enveloped RNA viruses by interrupting virus-endosomal fusion. However, antiviral activity of IFITM proteins against mammalian DNA virus has not been demonstrated till date. Here, we sought to investigate the antiviral activities and mechanisms of IFITM3 protein against poxvirus infection. Analysis of expression kinetics of cell endogenous IFITM3 protein indicated that vaccinia virus (VACV) infection suppressed its translation, which was independent of IRF3 phosphorylation triggered by VACV. Although silencing of endogenous IFITM proteins did not affect their baseline antiviral effects in the cell, it has reduced the IFN-α-mediated inhibition of VACV infection, and also modulated VACV-induced cell death. Moreover, we discovered that over-expression of IFITM3 significantly restricted VACV infection, replication and proliferation mainly by interfering with virus entry processes prior to the virus nucleocapsid entry into the cytoplasm. Interestingly, IFITM3 over-expression showed an impact on virus binding. Furthermore, IFITM3 interfered with the cytosolic entry of virus through low pH-dependent fashion. Taken together, our findings provide the first evidence of exogenously expressed IFITM3 protein restricting infection of an enveloped DNA virus, thus expanding their antiviral spectrum. This study further explores the complex mechanism and provides novel insights into the interaction between virus infection and host defense.